Socio-Economic Impact of Biogas Technology in Rural Nepal: A Case of Raptisonari Rural Municipality, Banke, Nepal - Acharya, Bishweshwar Prasad (Academia Research Journal, 2025)
This study investigates the socio-economic impacts of biogas technology in Raptisonari Rural Municipality ward no. 1 and 2 of Banke District, Nepal. In a nation where rural households heavily rely on traditional fuels—leading to deforestation, time poverty, and health hazards—biogas has emerged as a sustainable alternative. Employing descriptive research design, the study examines 30 households out of 150 biogas plant adopters using survey questionnaires, interviews, and focus group discussions. The research highlights that 100% of the plants were connected with toilets, indicating integration of sanitation and energy solutions. Time savings averaged 3.7 hours per day, particularly for women, who reported improved health and greater participation in social and productive activities. Health expenditures for common ailments declined significantly after biogas adoption, while annual household income exceeded NPR 100,000 for 40% of users. Biogas adoption also reduced firewood use by 90 kg/month and improved school attendance and study time for girls. Despite some seasonal underfeeding of plants and increased mosquito prevalence, overall satisfaction with biogas technology remains high. The study concludes that biogas offers multifaceted socio-economic benefits, and recommends broader policy and institutional support to expand its adoption among economically disadvantaged groups, particularly in similar agro-rural regions of Nepal.